Some Features Of Cardiac Activity In Young Men Living In The Conditions Of Karakalpakstan - Rzaev Raxat Muratbaevich (Zien Journals, 2024)
The study investigates the impact of environmental factors on the functional state of the human body, particularly focusing on young men living in Karakalpakstan. It analyzes the mechanisms of heart rate regulation and the adaptive reactions of the cardiorespiratory system. The research includes an evaluation of heart rate variability, systolic and diastolic blood pressure, and regulatory system activity. The findings highlight the influence of different environmental conditions and seasonal changes on the physiological functions of young men, providing essential insights into the adaptive mechanisms and health status of the population in this region
Keywords: environmental factors; cardiorespiratory system; heart rate variability